2007
DOI: 10.1097/mpa.0b013e318053e7d3
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, Occupational, and Reproductive Factors in Relation to Pancreatic Cancer Risk

Abstract: Multiple tobacco consumption methods, passive smoking, pesticide exposures, and diabetes are associated with an increased risk for pancreatic cancer. Prolonged lactation and increased parity are associated with a reduced risk for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 61 publications
2
83
1
Order By: Relevance
“…No significant relation with breastfeeding was found in a cohort study of younger women with shorter overall breastfeeding times (Skinner et al, 2003), while a case -control study, including extended breastfeeding periods, showed an inverse relation (Lo et al, 2007) consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant relation with breastfeeding was found in a cohort study of younger women with shorter overall breastfeeding times (Skinner et al, 2003), while a case -control study, including extended breastfeeding periods, showed an inverse relation (Lo et al, 2007) consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Others showed a higher (Karlson et al, 1998;Navarro Silvera et al, 2005) or lower (Hanley et al, 2001;Teras et al, 2005) risk among women with many children only or even no association with parity (Duell and Holly, 2005;Prizment et al, 2007). Breastfeeding was covered in only two studies (Skinner et al, 2003;Lo et al, 2007) while menstrual factors have shown inconclusive findings (Prizment et al, 2007).…”
mentioning
confidence: 99%
“…A case-control study by An-chi lo et al (39) showed that smoking increased the risk of pancreatic cancer with an OR of 4.5 (95%CI [1. 9-10.7]) for smokers who ever smoked cigarettes only, and an OR of 7.8 (95%CI [3.0 to 20.6]) for smokers who ever used multiple types of tobacco smoking.…”
Section: Complications Of Smokingmentioning
confidence: 99%
“…pdf) and three case-control (Villeneuve et al, 2004;Hassan et al, 2007;Lo et al, 2007; the former two studies are summarized in Table 2.18 available at http://monographs.iarc.fr/ENG/ Monographs/vol100E/100E-02-Table2.18.pdf).…”
Section: Cancer Of the Pancreasmentioning
confidence: 99%
“…(RR 1.2 (95%CI: 0.45-3.1) and 1.21 (95%CI: 0.60-2.44) respectively). Lo et al (2007) reported an odd ratio of 6.0 (95%CI: 2.4 −14.8) for never smokers (both sexes combined) exposed to second-hand tobacco smoke in Egypt. [The Working Group noted the small numbers of cases, the use of hospital controls and the small proportion of the cases (35%) with histopathological confirmation.…”
Section: (A) Exposure In Adulthoodmentioning
confidence: 99%